Citric acid as a green additive to retard calcium carbonate scales on process equipment. (2nd July 2020) - Prisciandaro, Marina; Mazziotti di Celso, Giuseppe; Lancia, Amedeo; Musmarra, Dino; Karatza, Despina
Abstract: In this paper, the retarding effect of a green additive, citric acid, towards calcium carbonate scale deposition is studied. Scale formation is one of the most common causes of malfunctions in process equipment. This is the reason it is crucial to retard scale precipitation, that is, in order to reduce economic damages. With this additive in the solution, experimental runs have been carried out in supersaturation conditions in terms of concentration of calcium carbonate at equilibrium, with a supersaturation ratio ranging from 16 to 280, at 25°C. Three different concentrations of citric acid have been investigated (0.520 × 10 −3, 1.041 × 10 −3 and 1.561 × 10 −3 M) in a laboratory scale plant. Comparing results obtained in terms of induction time with previous experimental runs, performed without additives, citric acid has shown its significant capacity to retard calcium carbonate precipitation, by increasing induction time values. This behaviour is enhanced by raising the additive concentration in solution up to a specific threshold value, beyond which no benefit in terms of calcium scale inhibition is gained. Furthermore, interfacial tension has been computed without and with citric acid at 0.520 × 10 −3 and 1.041 × 10 −3 M, as a function of the different concentration amounts investigated. The values obtained are in good agreement with data reported in the literature.